The unintended consequences of clinical trials regulations. - Alex D McMahon (Public Library of Science (PLoS), 2009)
Alex McMahon and colleagues critique the International Conference on Harmonisation (ICH) guidance on good clinical practice (GCP), arguing that it is having a disastrous effect on noncommerical randomized clinical trials in Europe.